2022
DOI: 10.21037/tlcr-22-391
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning the lung field based on the depth ratio in three-dimensional space

Abstract: Background: To explore the feasibility of the depth ratio method partitioning the lung parenchyma and the depth distribution of lung nodules in pulmonary segmentectomy.Methods: Based on the measurement units, patients were allocated to the chest group, the lobar group, and the symmetrical 3 sectors group. In each unit, the center of the respective bronchial cross-section was set as the starting point (O). Connecting the O point with the center of the lesion (A) and extending to the endpoint (B) on the pleural,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…19 In 2022, we published a study in the Journal of Translational Lung Cancer Research on the factors influencing the measurement accuracy of this method in each lung lobe and pointed out that the depth ratio method could accurately distinguish the inner, middle, and outer band ranges in three-dimensional space and eliminate the interference of mediastinal structures, to the greatest extent, in the three symmetrical partitions of the bilateral lungs. 20 The present study found a significant correlation between the probability of lymph node metastasis and the tumor's location within the inner (depth ratio >66.7%) zones, which aligns with the findings of Kawamoto et al 9 Conversely, Tane et al 21 did not observe a significant difference in the rate of lymph node metastasis between internal and external lesions. Additionally, DuComb et al 22 analyzed the NLST database to investigate the relationship between the coordinate position of solid nodules measuring 8-30 mm and N2/N3 lymph node metastasis.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…19 In 2022, we published a study in the Journal of Translational Lung Cancer Research on the factors influencing the measurement accuracy of this method in each lung lobe and pointed out that the depth ratio method could accurately distinguish the inner, middle, and outer band ranges in three-dimensional space and eliminate the interference of mediastinal structures, to the greatest extent, in the three symmetrical partitions of the bilateral lungs. 20 The present study found a significant correlation between the probability of lymph node metastasis and the tumor's location within the inner (depth ratio >66.7%) zones, which aligns with the findings of Kawamoto et al 9 Conversely, Tane et al 21 did not observe a significant difference in the rate of lymph node metastasis between internal and external lesions. Additionally, DuComb et al 22 analyzed the NLST database to investigate the relationship between the coordinate position of solid nodules measuring 8-30 mm and N2/N3 lymph node metastasis.…”
Section: Discussionsupporting
confidence: 91%
“…In 2021, we published our study in the Chinese Journal of Thoracic and Cardiovascular Surgery, which used the “depth ratio” method, to analyze the differences in the location recognition of pulmonary nodules in two‐ and three‐dimensional images, and discussed the method and clinical significance of determining the location of the pulmonary nodules in three‐dimensional space 19 . In 2022, we published a study in the Journal of Translational Lung Cancer Research on the factors influencing the measurement accuracy of this method in each lung lobe and pointed out that the depth ratio method could accurately distinguish the inner, middle, and outer band ranges in three‐dimensional space and eliminate the interference of mediastinal structures, to the greatest extent, in the three symmetrical partitions of the bilateral lungs 20 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, anatomical sublobar resection has been gradually promoted for clinical application in thoracic surgery. The key technique of lung segmentectomy is to distinguish the anatomical structure of lung vessels and bronchi by 3D CT reconstruction technology ( 23 , 36 ). Therefore, most thoracic surgeons who perform thoracoscopic lung segmentectomy begin with the fissure-first approach.…”
Section: Discussionmentioning
confidence: 99%
“…The eligible medical records were subjected to comparative and analytical examinations encompassing various variables, including patient age, sex, nodule size (cm), nodule location, nodule solid component, nodule depth ratio, number of intrapulmonary lymph nodes sampled, surgical margin distance (cm), operation time (min), intraoperative bleeding (ml), number of conversions to thoracotomy, counts of lung subsegments resected, postoperative hospital stay (days), and occurrence of postoperative lung air leakage. The depth ratio method was used for the three symmetrical sectors ( 23 ).…”
Section: Methodsmentioning
confidence: 99%